Strategic Factors in Balance of Payments Adjustment: Comment - Machlup, Fritz (The Review of Economics and Statistics, 1958)
Fritz Machlup, Strategic Factors in Balance of Payments Adjustment: Comment, The Review of Economics and Statistics, Vol. 40, No. 1, Part 2. Problems in International Economics (Feb., 1958), pp. 137-140